Binding of Excreted and/or Secreted Products of Adult Hookworms to Human NK Cells in Necator americanus-Infected Individuals from Brazil - Teixeira-Carvalho, Andréa (American Society for Microbiology (ASM), 2008)
The impact of the interaction between excreted and/or secreted (ES) Necator americanus products and NK cells from Necator-infected individuals was analyzed. We investigated the binding of ES products to NK cells, the expression of NK cell receptors (CD56, CD159a/NKG2A, CD314/NKG2D, CD335/NKp46, and KLRF1/NKp80), the frequency of gamma interferon (IFN-γ)-producing NK cells after whole-blood in vitro stimulation, and the capacity of N. americanus ES products to induce NK cell chemotaxis. In contrast to those from noninfected individuals, NK cells from Necator-infected individuals demonstrated no binding with N. americanus ES products. This phenomenon was not due to alterations in NK cell receptor expression in infected subjects and could not be reproduced with NK cells from uninfected individuals by incubation with immunoregulatory cytokines (interleukin-10/transforming growth factor β). Further, we found that a significantly greater percentage of NK cells from infected subjects than NK cells from uninfected individuals spontaneously produced IFN-γ upon ex vivo culture. Our findings support a model whereby NK cells from Necator-infected individuals may interact with ES products, making these cells refractory to binding with exogenous ES products. During N. americanus infection, human NK cells are attracted to the site of infection by chemotactic ES products produced by adult Necator worms in the gut mucosa. Binding of ES products causes the NK cells to become activated and secrete IFN-γ locally, thereby contributing to the adult hookworm's ability to evade host immune responses.